Enterolobium barnebianum A.L. Mesquita & M.F. da Silva, uma nova Mimosácea para a Amazônia brasileira, Colômbia e Peru. - Mesquita, Antônio L.; Silva, Marlene Freitas da (Acta Amazonica, 1984)
Enterolobium barnebianum A.L. Mesquita & M.F. da Silva is described as a new species, occuring in the Amazoniam region of Brazil and neighboring countries.